Response of irish creamery milk supply to price changes - Cuddy, Michael (Economic & Social Studies, 1982)
Precis: This article investigates the responsiveness of creamery milk supply to changes in the price of milk relative to agricultural materials. A basic model, which includes milk and livestock price variables and a Gini co-efficient of cow concentration (a proxy for technological change) is modified to test pre- and post-EEC response differences. The effects of the milk price variables are isolated using the method of principal components. Price responsiveness was higher in the post- than pre-EEC period with largest responses shown after a two to three year lag. The technology effect although positive was not significant.
Keywords: Economics; Agriculture - Dairy